Proteomics of acquired enamel pellicle and saliva in patients with gastroesophageal reflux disease with or without erosive tooth wear and in vitro evaluation of the protective potential of hemoglobin against initial erosion - Martini, Tatiana (2021)
This study compared the proteomic profile of the acquired enamel pellicle (AEP) of the palatal/lingual region and unstimulated saliva of patients (1) with gastroesophageal reflux disease (GERD) and erosive tooth wear (ETW) (BEWE, score 9; GE Group); (2) with GERD without ETW (BEWE = 0; GNE group); (3) without GERD without ETW (BEWE=0, Control group) using label-free shotgun quantitative proteomic analysis (nLC-ESI-MS / MS). Since in preliminary experiments we observed increased expression of different Hb subunits in patients with GERD without ETW when compared with patients with GERD and ETW, we also evaluated, in vitro, the potential of AEP modification with different concentrations of hemoglobin (Hb) to protect enamel against initial erosion. After prophylaxis, AEP was allowed to form for 120 min. The AEP was collected from the palatal/lingual surface with filter paper soaked in 3% citric acid. After extraction, proteins were identified by nLC-ESI-MS / MS. A total of 213 proteins were identified in the AEP. The GNE group had a high number of phosphorylated and calcium-binding proteins, in addition to Spectrin beta-chain isoforms found exclusively in this group. Regarding the proteomics of saliva, when the GNE group was compared with the GE group, a remarkable increase in distinct Hb subunits was observed (up to 22 times). Other increased proteins were Serum albumin (4.5-fold) and type II cytoskeletal keratin isoforms (more than 3-fold). Proteinase inhibitors, such as Alpha-1-antitrypsin and Alpha-2-macroglobulin, were identified exclusively in the GNE group. In the in vitro study, Hb at 1.0 and 4.0 mg/mL significantly reduced initial enamel erosion after 3 days. These results indicate that many proteins may be involved in the resistance of GERD patients to the ETW, with special emphasis on hemoglobin, in addition to intracellular proteins that have the potential to bind to hydroxyapatite or participate in the formation of supramolecular aggregates. These proteins may be candidates for inclusion in dental products for protection against ETW. Data from the in vitro study indicate that changing the composition of AEP by enriching with Hb at 1.0 mg/mL might be a good strategy for protection against intrinsic erosion.